2012
DOI: 10.1128/iai.00385-12
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Aggregatibacter actinomycetemcomitans Cytolethal Distending Toxin Subunits during Intoxication of Live Cells

Abstract: The cytolethal distending toxin (Cdt), produced by some clinically important Gram-negative bacterial species, is related to the family of AB-type toxins. Three heterologous proteins (CdtA, CdtB, and CdtC) and a genotoxin mode of action distinguish the Cdt from others in this toxin class. Crystal structures of several species-specific Cdts have provided a basis for predicting subunit interactions and functions. In addition, empirical studies have yielded significant insights into the in vivo interactions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 37 publications
9
52
1
Order By: Relevance
“…It should be pointed out that in a more recent study in which Cdts from different microbial species were studied simultaneously, fucosylated structures as well as N-and O-glycans were found not to be required for Cdt-host cell interaction (40). In contrast, these authors observed that Cdt derived from three sources, A. actinomycetemcomitans, C. jejuni, and H. ducreyi, were each dependent upon membrane cholesterol, thereby confirming the previous observations of BoeszeBattaglia et al (33) other investigators who have reported that cholesterol depletion failed to alter toxin subunit internalization (41). It should be noted that this study, by Damek-Poprawa et al, is difficult to assess with respect to the role of cholesterol as the experimental protocol utilized a long exposure time to methyl-␤-cyclodextrin, and, further, cholesterol repletion was not employed to demonstrate specificity.…”
Section: Discussionsupporting
confidence: 79%
“…It should be pointed out that in a more recent study in which Cdts from different microbial species were studied simultaneously, fucosylated structures as well as N-and O-glycans were found not to be required for Cdt-host cell interaction (40). In contrast, these authors observed that Cdt derived from three sources, A. actinomycetemcomitans, C. jejuni, and H. ducreyi, were each dependent upon membrane cholesterol, thereby confirming the previous observations of BoeszeBattaglia et al (33) other investigators who have reported that cholesterol depletion failed to alter toxin subunit internalization (41). It should be noted that this study, by Damek-Poprawa et al, is difficult to assess with respect to the role of cholesterol as the experimental protocol utilized a long exposure time to methyl-␤-cyclodextrin, and, further, cholesterol repletion was not employed to demonstrate specificity.…”
Section: Discussionsupporting
confidence: 79%
“…5), whereas neither CdtB subunit was associated with either the cytosolic or microsomal fractions. In contrast to the CdtB subunits, neither the CdtA nor CdtC subunits of Ec-CDT or Hd-CDT were detected within the nuclear fractions (data not shown), which is consistent with the model that only the A fragments of retrograde-trafficked bacterial toxins are translocated out of the ER (9) and, more recently, with immunofluorescence studies of the intracellular trafficking of CDT from A. actinomycetemcomitans (47).…”
Section: Effects Of Endosomal Acidification Inhibitors On Cdtb Localisupporting
confidence: 88%
“…We speculate that the levels of Ec-CdtB and Hd-CdtB within the cytosol in these experiments were below our detection limits. A recent study reported the detection of a fluorescent version of CdtB from A. actinomycetemcomitans within the cytosol and nucleus (47). However, in another recent study (68), the authors suggested that Hd-CdtB localization to the nucleus does not require that this subunit first be translocated to the cytosol.…”
Section: Discussionmentioning
confidence: 96%
“…The Aggregatibacter CDT was found to be functional, albeit with a reduced titre, when lacking the A (Akifusa et al, 2001) or the C subunit (Saiki et al, 2001). These findings were later explained by the work of Damek-Poprawa et al (2012) who reported that after the internalisation of CdtB, CdtA remains on the cell surface, while CdtC migrates into the cytosol, suggesting that it acts as a chaperone to CdtB. In the present study, the slight decrease in cell mass observable in HeLa cultures after 3 days of exposure to supernatants containing CdtB + CdtC combination, and more noticeably in the case of CdtB + CdtA, might suggest similar mechanisms.…”
Section: Discussionsupporting
confidence: 54%